Aktivitas Antioksidan dari Ekstrak Kulit Buah Manggis dengan Metode Sonikasi - Elvina Legia Helisa; Lanny Mulqie; Arlina Prima Putri (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Mangosteen grows in tropical countries, such as Malaysia, Thailand, and Indonesia. Mangosteen (Garcinia mangostana L.) has widespread pharmacological potential especially in the utilization of its fruit rind. The fruit contains bioactive compounds, such as xanthones and anthocyanins, which are mainly extracted from the rind. In addition, mangosteen has high antioxidant properties in helping neutralize free radicals. This study aims to establish the IC50 value of mangosteen rind extracts extracted with aquadest and ethanol using sonication method and determine that ethanol or aquadest extracts of mangosteen rind are more effective in providing antioxidant activity based on DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The extraction process was carried out using 96% ethanol and aquadest sonicated for 45 minutes and 90 minutes. The results of antioxidant activity testing conducted by DPPH method showed that the IC50 value of sonication extraction in 96% ethanol solvent and aquadest were 10.28 ppm and 46.52 ppm respectively. This indicates that the antioxidant activity of mangosteen rind using sonication method with 96% ethanol solvent and aquadest can still be categorized as very strong. The low IC50 value of mangosteen fruit peel ethanol extract compared to the IC50 value of mangosteen fruit peel aquadest extract indicates that the ethanol extract of mangosteen fruit peel has higher antioxidant activity and is more effective in reducing free radicals.